Oral vinorelbine in the treatment of non-small-cell lung cancer. (August 2014) - Barletta, Giulia; Genova, Carlo; Rijavec, Erika; Burrafato, Giovanni; Biello, Federica; Sini, Claudio; Dal Bello, Maria Giovanna; Coco, Simona; Truini, Anna; Vanni, Irene; Alama, Angela; Beltramini, Sabrina; et al.
Abstract : Introduction: Originally formulated as an intravenous (i.v.) agent, vinorelbine is also currently available as an oral chemotherapeutic agent. Oral vinorelbine has demonstrated significant activity in different settings for NSCLC, including adjuvant treatment for resected disease, concurrent chemoradiation for locally advanced NSCLC and palliative chemotherapy for recurrent/metastatic NSCLC, as part of combination schedules or as a single-agent treatment. Areas covered: The authors explored the available data describing the use of oral vinorelbine in NSCLC. PubMed articles and abstracts presented at international conferences were analysed, and relevant trials were reported and discussed. Specific settings, including the treatment of elderly and unfit patients and metronomic schedules including oral vinorelbine, were evaluated. Available pharmacoeconomic data were also assessed. Expert opinion: Oral vinorelbine is an appealing agent, particularly as part of combination regimens containing platinum derivatives, although it can have a role as a single-agent treatment as well. Its safety profile is generally favourable and its route of administration is generally preferred by patients receiving chemotherapy. Compared to i.v. vinorelbine and other antineoplastic agents, oral vinorelbine has been reported to be advantageous in terms of cost savings.